Negotiating Political Conflicts - Pfetsch, F. author. aut Link
XIV, 216 p.
Keywords: Negotiating Political Conflicts analyzes comprehensively the foundations for understanding negotiations: What is negotiation? What are the most important concepts and terms? Empirical examples illustrate theoretical conceptions. Academics and practitioners will find this book an invaluable companion to the theory and practice of negotiation.